2003
DOI: 10.1200/jco.2003.04.197
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation Docetaxel After Concurrent Chemoradiotherapy in Stage IIIB Non–Small-Cell Lung Cancer: Phase II Southwest Oncology Group Study S9504

Abstract: Consolidation docetaxel after concurrent chemoradiotherapy in stage IIIB NSCLC is feasible and generally tolerable, and results compare favorably with the predecessor trial S9019. Nevertheless, this study remains hypothesis-generating and does not provide definitive evidence of the benefit of this approach. Phase III trials evaluating the S9504 regimen have been initiated to validate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
184
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 342 publications
(193 citation statements)
references
References 26 publications
5
184
0
4
Order By: Relevance
“…This study has demonstrated encouraging survival in the cooperative group setting with 37% of patients alive at 3 years (25).…”
Section: Discussionmentioning
confidence: 96%
“…This study has demonstrated encouraging survival in the cooperative group setting with 37% of patients alive at 3 years (25).…”
Section: Discussionmentioning
confidence: 96%
“…Sekine I and Nokihara H revealed that cisplatin, vinorelbine concurrent TRT before docetaxel consolidation therapy resulted in 81, 81, 10, 10% of patients associated with grade 3/4 leukopenia, neutropenia, pneumonitis, esophagitis in unresectable stage III NSCLC [25]. Gandara DR and Chansky K demonstrated that cisplatin and S-1 with concurrent TRT in unresectable stage III NSCLC patients undergone grade 3/4 leukopenia in 50%, neutropenia in 25%, pneumonitis in 26% of patients [26]. A Japanese study reported that cisplatin or carboplatin, paclitaxel and docetaxel with concurrent RT resulted in an incidence of 13% acute grade 3/4 pneumonitis toxicity and 13% grade 3/4 esophageal toxicity in stage III elderly NSCLC patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…The current role of consolidation chemotherapy following either high-dose palliative or radical CRT has not been established. Two phase II trials, one of which was a three-arm randomised study, have suggested an improved survival with the addition of consolidation chemotherapy to radical CRT relative to CRT alone (Choy et al, 2002;Gandara et al, 2003). Within the limits imposed by a phase I trial design, the regimen has demonstrated promising efficacy, with a overall radiological response rate (in and out of field) of 65% (15/23) comprising of CR in 4% (one) and PR in 61% (14).…”
Section: Discussionmentioning
confidence: 99%